A comprehensive overview of the ADALINE method applied to rapid voltage sags detection in multi-motors drive systems - Mounir Bensaid; Abdellfattah Ba-Razzouk; Mustapha Elharoussi (Institute of Advanced Engineering and Science, 2022)
Several strategies have been developed for identifying power quality issues, monitoring them, and compensating for relevant disturbances. In this field, online estimate of amplitudes and phase angles of network voltages and currents is commonly used. The adaptive linear neuron (ADALINE)-based voltage sag detection algorithm with least mean square (LMS) adaptation allows for rapid convergence of estimate techniques based on artificial neural networks (ANN). This approach has the advantage of being straightforward to implement on hardware and based on simple calculations (essentially multiply and accumulate